The Effect of Mindfulness Based Cognitive Therapy (MBCT) for Optimizing Efficacy Self-Care in Cancer Patients Undergoing Treatment - Rovica Probowati; Witriyani Witriyani; Andriani Mei Astuti; Veren Pinka Nabila (Indonesian Journal of Global Health Research, 2025)
Cancer is a disease that can threaten a person's life which can occur in every cancer sufferer, apart from that cancer can also cause psychological problems such as low efficacy of patient self-care which will have an impact on treatment compliance in cancer patients.Objective: The aim of this study was to determine the effect of the MBCT intervention on whether it could increase self-care efficacy in cancer patients undergoing cancer treatment. Method: The method used in this research is an experiment with a pretest-posttest design with control group design. The research subjects were 20 people who were divided into experimental and control groups with inclusive. Data analysis used the Wilcoxon and Mann-Whitney tests. Results: The results showed an increase in self-care efficacy after administering the mindfulness-based cognitive therapy (MBCT) intervention with a self-care efficacy value of Z = -2.660 and p = 0.008. Conclusions: The research results show that mindfulness based cognitive behavior therapy (MBCT) can increase patient confidence in carrying out treatment regularly. Cancer patients who Applying MBCT in everyday life they can also feel the effects such as tense muscles becoming more comfortable, better conscious breathing begins to feel the impact on the subject's calmness, and increased ability to detect the body. Mindfulness-based cognitive therapy (MBCT) changes the behavior of each participant to be able to accept themselves in any situation, more easily adapt to changes that occur in their physical and life and establish social relationships with other people.